Scoping Review: Pengaruh Pemberian Sediaan Kacang Kedelai terhadap Gejala Hot Flushes pada Pasien Menopause - Mutiara Salsa Ervina; Hidayat Widjajanegara; Dean Wahjudy Satyaputra (UNISBA Press, 2022)
Abstract. Menopause is characterized by a decrease in estrogen that can cause unpleasant symptoms such as hot flushes, night sweats, sleep disorders, and vaginal dryness. Of these menopausal symptoms, many women report that hot flashes are the most troublesome. The most effective treatment for menopausal symptoms is hormone therapy (HT). However, the use of hormone therapy is declining due to many proven side effects, such as an increased risk of uterine cancer and breast cancer. Several complementary and alternative therapies, such as herbal estrogens, are widely used to treat menopausal symptoms. Plant-based estrogens, or phytoestrogens (such as soybeans), are a reliable source of isoflavones that help relieve menopausal symptoms. The purpose of the study was to analyze the effect of giving soybean preparations on the symptoms of hot flushes. This study uses a scoping review to analyze scientific writings from four data sources, namely Science direct, Springer link, Pubmed and ProQuest. The initial search resulted in 1,035 articles, and 5 articles that were eligible (elegible) were summarized in the PRISMA diagram. The PICOS criteria in this study were Population (menopausal women), Intervention (given phytoestrogens from soybeans), Comparison (patients who were not given phytoestrogens from soybeans), Outcome (complaints of Hot Flushes in postmenopausal patients), and Study (Randomized Control Trial). Analysis of five articles showed that regular intake of phytoestrogens from soybeans led to a significant reduction in hot flushes over placebo in four articles. In addition, there is an article stating that taking isoflavones from soy does not significantly change the symptoms of hot flushes. The conclusion of this study showed that consumption of preparations from soybeans was more effective in reducing the symptoms of hot flushes. Abstract. Menopause ditandai dengan penurunan estrogen, yang dapat menyebabkan gejala tidak nyaman seperti hot flushes, keringat malam, gangguan tidur, dan kekeringan pada vagina.. Gejala menopause yang paling banyak dilaporkan sangat mengganggu adalah hot flushes. Pengobatan yang paling efektif untuk mengurangi gejala menopause adalah terapi hormon (HT). Namun, karena banyak efek samping yang terbukti, seperti peningkatan risiko kanker rahim dan kanker payudara, penggunaan untuk terapi hormon telah menurun. Beberapa terapi pengobatan komplementer dan alternatif seperti estrogen herbal telah banyak digunakan untuk mengatasi masalah menopause. Estrogen herbal atau fitoestrogen seperti kedelai adalah sumber isoflavon yang dapat diandalkan untuk mengurangi gejala menopause. Tujuan penelitian untuk menganalisis pengaruh pemberian sediaan kacang kedelai terhadap gejala hot flushes pada pasien menopause. Penelitian ini menggunakan scoping review untuk menganalisis tulisan ilmiah dari empat sumber data yaitu Science direct, Springer link, Pubmed dan ProQuest. Pada pencarian awal dihasilkan 1.035 artikel, dan artikel yang memenuhi kelayakan (elegible) ada 5 artikel dirangkum dalam diagram PRISMA. Kriteria PICOS dalam penelitian ini adalah Population ( wanita menopause), Intervention ( pemberian fitoestrogen dari kacang kedelai), Comparison ( pasien yang tidak diberikan fitoestrogen dari kacang kedelai), Outcome ( keluhan hot flushes pada pasien menopause), dan Study (Randomized Control Trial). Hasil analisis dari 5 artikel menunjukkan empat artikel menyatakan konsumsi rutin fitoestrogen dari kacang kedelai menghasilkan pengurangan jumlah hot flushes yang jauh lebih tinggi dari pada plasebo. Selain itu, terdapat satu artikel menyebutkan konsumsi isoflavones dari produk olahan kedelai tidak menyebabkan perubahan yang signifikan terhadap gejala hot flushes. Kesimpulan pada penelitian ini menunjukkan konsumsi sediaan dari kacang kedelai lebih efektif dalam mengurangi gejala hot flushes.